Faktor yang Mempengaruhi Respon Petani Terhadap Penggunaan Pupuk Ireng-Ireng Di Kecamatan Wuluhan Kabupaten Jember - Pudjiastutik, Endang Wahyu; Septianingtyas Purwandhini, Ari; Kurniawan, Deddy (Hasanuddin University, 2025)
Wuluhan District, Jember Regency, is one of the regions with strong agricultural potential, particularly in rice production. However, in recent years, farmers in this area have faced various challenges, including declining soil fertility, increasing production costs, and climate change. One of the efforts to improve soil fertility and reduce production expenses is the use of organic fertilizers. Another ongoing issue concerns the supply and distribution of fertilizers, which has yet to be fully resolved. One of the fertilizers currently being developed by a local farmer in Wuluhan District is Ireng-Ireng fertilizer. Therefore, this study aims to identify the factors that influence farmers’ responses to the use of Ireng-Ireng fertilizer in rice cultivation in Wuluhan District. An ordinal regression approach using the Polytomous Universal Model (PLUM) was applied to assess the effects of internal and external farmer-related variables on response levels categorized as low, medium, and high. The findings indicate that the regression model is statistically valid and meets all required assumptions. Three variables—land size, income, and farming experience—significantly affect farmers’ response levels, while age, formal education, non-formal education, perceived speed of results, and perceived costs show no significant effects. Overall, farmers exhibit a positive response toward the use of Ireng-Ireng fertilizer in terms of knowledge, attitude, and actual use. These results highlight that farmers’ internal capacities play a crucial role in the adoption of local organic fertilizers, which hold strong potential to support sustainable rice farming.